2023
DOI: 10.3847/1538-4357/acbeac
|View full text |Cite
|
Sign up to set email alerts
|

Dust-buried Compact Sources in the Dwarf Galaxy NGC 4449

Abstract: Multiwavelength images from the Hubble Space Telescope covering the wavelength range 0.27–1.6 μm show that the central area of the nearby dwarf galaxy NGC 4449 contains several tens of compact sources that are emitting in the hydrogen recombination line Paβ (1.2818 μm) but are only marginally detected in Hα (0.6563 μm) and undetected at wavelengths λ ≤ 0.55 μm. An analysis of the spectral energy distributions (SEDs) of these sources indicates that they are likely relatively young stellar clusters heavily atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 132 publications
3
10
1
Order By: Relevance
“…The overall pattern, however, is the same as in the other objects. The situation we find in the majority of the IMPs is remarkably similar to that in other metal-poor DGs, where this two-stage starburst scenario appears to be linked to superbubbles and galactic outflows, for instance in NGC 1569 (Heckman et al 1995;Vallenari & Bomans 1996;Origlia et al 2001) or NGC 5253 (Monreal-Ibero et al 2010;Calzetti et al 2015). Several LCGs, such as the GPs studied by Amorín et al (2012), have been shown to have a similar SFH.…”
Section: Star-formation Historiessupporting
confidence: 80%
“…The overall pattern, however, is the same as in the other objects. The situation we find in the majority of the IMPs is remarkably similar to that in other metal-poor DGs, where this two-stage starburst scenario appears to be linked to superbubbles and galactic outflows, for instance in NGC 1569 (Heckman et al 1995;Vallenari & Bomans 1996;Origlia et al 2001) or NGC 5253 (Monreal-Ibero et al 2010;Calzetti et al 2015). Several LCGs, such as the GPs studied by Amorín et al (2012), have been shown to have a similar SFH.…”
Section: Star-formation Historiessupporting
confidence: 80%
“…We do not expect that discarding low-mass young clusters will affect our conclusions, which are based on sources with masses 3000 M e (see Section 7). We note that we do not recover any of the sources identified by Calzetti et al (2023); none of the 34 sources selected by those authors show evidence for emission in Paα, although they are sufficiently compact to be indistinguishable from stellar sources and therefore part of the stellar population in this galaxy. After applying both of our selection criteria, we are left with 99 sources (21% of the original sample) that display Paα emission, with >90% of them detected with S/ N > 7 in this line.…”
Section: Confirmation Of Sources With Jwst Datacontrasting
confidence: 65%
“…Messa et al (2021) were however restricted by the requirement that sources still need to be detectable at optical wavelengths in order to determine their ages and masses. Calzetti et al (2023), using HST optical and IR images of NGC 4449, attempted to obtain a sample of highly extincted clusters by selecting sources that emit at Paβ but are undetected at optical and shorter wavelengths. The specific selection requirements used in that study resulted in a limited number of sources (34) with a narrow range of properties, which leaves open the question of whether those authors' approach includes potential biases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations